Cover Image, Volume 120, Number 8, December 1, 2019. Issue 8 (26th November 2019) - Wang, Yifei; Liang, Weiming; Qu, Shan; Zhang, Yidan; Du, Zhiye; Ji, Tao; Qu, Huayi; Gorlick, Richard; Guo, Wei
Abstract : The cover image is based on the Research Article Assessment of patient experiences following total sacrectomy for primary malignant sacral tumors: A qualitative study by Yifei Wang et al., https://doi.org/10.1002/jso.25756 . Cover image © Department of Musculoskeletal Tumors, Peking University People's Hospital Images